PENGARUH KOMBINASI PUPUK HAYATI DAN DOSIS NPK TERHADAP PERTUMBUHAN DAN HASIL JAGUNG MANIS - Bayu Handoko; Bagus Nur Rochman; Rifqi Adisonda (AGRORADIX : Jurnal Ilmu Pertanian, 2023)
Sweet corn productivity can be achieved by increasing land productivity which is supported by the suitability of land and climate conditions. The use of biological fertilizers and NPK fertilizers is an effort to increase land productivity. The purpose of this study was to determine the effect of the combination of biological fertilizers, NPK fertilizer doses, and interactions on the growth and yield of sweet corn. The research design used a completely randomized design (CRD) with three replications. The factors that were tried were the combination of biological fertilizers A and B (H1), A and C (H2), B and C (H3), A, B, and C (H4) and the dose of NPK fertilizer was 100% (D1), 75% ( D2), 50% (D3), 25% (D4) of the recommended dose. The results of this study are that the combination of several types of biological fertilizers has not been able to increase the growth and yield of sweet corn plants, presumably due to antagonistic competence between biological fertilizers and one another. The dose of NPK fertilizer 75% of the recommendations had the best results on sweet corn yields because a lower dose of NPK fertilizer was able to increase the yield of sweet corn.